A numerical study: Transitional hydrodynamic behaviour of a moored barge in different ultra-shallow water depths of Malaysia - Patel, M.S. (Bentham Science Publishers, 2020)
Background: Malaysia has most of its oil reservoirs in the South China sea. The water depth ranges from 50 m to 200 m. The effects of ultra-shallow water are of prime importance in the exploration of marginal oil fields. Hence, there is an increasing demand for understanding the hydrodynamic behavior of FPSO in ultra-shallow water depths. Objective: A simulation study in both frequency-domain and time-domain analyses has been performed to understand the dynamic responses of a moored barge in varying shallow water depths. The objective of this study was to observe the transitional hydrodynamic behavior of the moored barge under varying shallow water depths. Methods: The moored barge was administered under regular and irregular waves. Operating conditions for irregular waves in terms of significant wave height and peak time period were incorporated from PETRONAS Technical Standards (PTS). The wave-body interactions and mooring effects have been numerically modelled using a commercial Computational Fluid Dynamics (CFD) and simulation software (ANSYS AQWA) successfully. In order to gain confidence in the simulation software, additional experimental validation was performed for a FPSO model. Results: Though the barge was primarily free to rotate in all Degrees Of Freedom (DOF), however, only three DOFs were considered for our study; viz, heave, roll and yaw respectively. The force spectral density, cable RAOâs in addition to the time series of cable forces, along with the effect of significant motions on the mooring cables behavior have been discussed. Conclusion: In irregular beam sea state, the significant motions in ultra-shallow water were greater than that for deep waters, this was primarily the main reason for higher cable responses in ultra-shallow water. Â© 2019 Patel et al.